Sapho : Manon Lescaut - Daudet, Alphonse; Prevost, Antoine Francois (New York : The modern library, 1919)
New National Theatre, W.H. Rapley, manager, Wm. H. Fowler, business manager, the world's greatest artiste Mme. Sarah Bernhardt and her own company, from the Theatre Sarah Bernhardt, Paris, in Repertoire, under the direction of W.F. Connor, "Sapho" piece en 5 actes, de Alphonse Daudet.
In: American theater programs of the late 19th and 20th centuries (Library of Congress).
Keywords: France Literature; Theater programs -- Washington (D.C.); Theater programs -- 1911.